2019
DOI: 10.1002/anie.201909461
|View full text |Cite
|
Sign up to set email alerts
|

Turning the Tap: Conformational Control of Quantum Interference to Modulate Single‐Molecule Conductance

Abstract: Together with the more intuitive and commonly recognized conductance mechanisms of charge‐hopping and tunneling, quantum‐interference (QI) phenomena have been identified as important factors affecting charge transport through molecules. Consequently, establishing simple and flexible molecular‐design strategies to understand, control, and exploit QI in molecular junctions poses an exciting challenge. Here we demonstrate that destructive quantum interference (DQI) in meta‐substituted phenylene ethylene‐type olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 53 publications
6
66
0
10
Order By: Relevance
“…However, charge transport simulations and scanning tunnelling microscopy break junction (STM-BJ) experiments showed that o,p-MeO is substantially more conductive than m-OPE3 or m,m-MeO, which have very similar properties. 36 The results for o,o-MeO are insightful; experimentally its conductance is lower than m,m-MeO and m-OPE3, but it can be shown computationally that its conductance can be "switched on" by altering the conformation of the methoxy substituent to a sterically unfavourable position in which an oxygen lone pair can interact with the π-system. This geometry gives conductance comparable to o,p-MeO.…”
Section: Breakdown Of Carsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, charge transport simulations and scanning tunnelling microscopy break junction (STM-BJ) experiments showed that o,p-MeO is substantially more conductive than m-OPE3 or m,m-MeO, which have very similar properties. 36 The results for o,o-MeO are insightful; experimentally its conductance is lower than m,m-MeO and m-OPE3, but it can be shown computationally that its conductance can be "switched on" by altering the conformation of the methoxy substituent to a sterically unfavourable position in which an oxygen lone pair can interact with the π-system. This geometry gives conductance comparable to o,p-MeO.…”
Section: Breakdown Of Carsmentioning
confidence: 99%
“…Jiang et al reported unusual QI behaviour in a combined experimental and computational study of meta-connected oligo( phenylene-ethynylene) (OPE) molecular wires substituted with methoxy groups at different positions on the central ring. 36 Here we will name their structures based on the relationship between the methoxy substituent and the two phenylene-ethynylene units bearing the sulfur-based anchoring groups; either ortho to one and para to the other (o,p-MeO), meta to both (m,m-MeO) or ortho to both (o,o-MeO) ( Fig. 5a).…”
Section: Breakdown Of Carsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Furthermore, unlessamolecule is electrostatically or electrochemically gated, the highest occupied andl owest unoccupiedm olecular orbitals (HOMOa nd LUMO,r espectively) levels adjust themselves such that the Fermie nergy of the electrodes lies in the vicinity of the middle of the HOMO-LUMO gap. [18,19] Consequently,i ft he core of the molecule is weakly coupled to the electrodes (e.g.,t hrough triple bonds, which link the core to an anchoring group), the electricalc onductancei sp roportional to (g ij ) 2 ,w here g ij is the amplitude of an electronic de Brogliew ave on atom j,d ue to electrons injected into the core at site i with energies close to the middle of the HOMO-LUMO gap. These concepts of weak coupling, connectivity and mid-gap transport have been utilized in as eries of papers to develop quantumc ircuit rules for materials discoverya nd to develop as implem agic ratio rule (MRR) [15] for describing the influence of connectivity on QI in heterocyclic PAHs.…”
Section: Introductionmentioning
confidence: 99%